The full‐length sequence of the novel HLA‐C*08:190 allele, identified by cloning and sequencing. (8th October 2020) - Zou, Hong‐Yan; Zhou, Dan
Abstract : C*08:190 differs from C*08:01:01:01 by one nucleotide change at nucleotide 503 in exon 3 from A to G.